Basal hydrofractures near sticky patches - Zhang, H; Katz, RF; Davis, T; Stevens, LA; May, DA (Cambridge University Press, 2022)
Basal crevasses are macroscopic structural discontinuities at the base of ice sheets and glaciers that arise by fracture. Motivated by observations and by the mechanics of elastic fracture, we hypothesise that spatial variations in basal stress (in the presence of basal water pressure) can promote and localise basal crevassing. We quantify this process in the theoretical context of linear elastic fracture mechanics. We develop a model evaluating the effect of shear-stress variation on the growth of basal crevasses. Our results indicate that sticky patches promote the propagation of basal crevasses, increase their length of propagation into the ice and, under some conditions, give them curved trajectories that incline upstream. A detailed exploration of the parameter space is conducted to gain a better understanding of the conditions under which sticky-patch-induced basal crevassing is expected beneath ice sheets and glaciers.